Corruption Risk Factors and Their Effect on the Interoceanic Highway in Peru - Mejía, Álvaro; Uribe, André; Florentino, Fabrizzio; Vásquez, Rafael; Moscoso, Julio; Acosta, Juan (Revista del CLAD Reforma y Democracia, 2021)
This study aims to analyze the relationship between performance and the exercise of corruption in the construction of the Southern Interoceanic, Sections II and III, which connects Peru with Brazil. The methodology used includes a bibliographic review and a case study. The selected literature emphasizes the relationship between risk factors in infrastructure megaprojects and the generic characteristics that define acts of corruption. On the other hand, the case study uses Merrow’s failure criteria for the development of construction megaprojects. It also examines whether exports along the highway contribute significantly to trade between Peru and Brazil. The results suggest that both the project and the context showed multiple risk factors during design, conception and execution, related to project failure in the cost overrun criteria. Meanwhile, the increase in export traffic on the highway has not been significant and is likely to have been caused by external factors that limit the success of the megaproject.